Emerging strategies for treatment of systemic sclerosis. Issue 2 (May 2016) - Khanna, Dinesh; Distler, Jörg H.W.; Sandner, Peter; Distler, Oliver
Systemic sclerosis is a heterogeneous condition characterized by microvascular damage, dysregulation of the immune system, and progressive fibrosis affecting skin and internal organs. Currently, there are no approved disease-modifying therapies, and management mostly involves treatment of organ-specific complications. In recent years, major advances have greatly improved our understanding of the disease process, especially the molecular mechanisms by which fibrosis becomes self-sustaining. We discuss selected aspects of these mechanisms with a focus on those relevant to ongoing efforts to develop disease-modifying therapies. We also discuss advances in identification of patient subtypes, and selected examples of potential disease-modifying therapies in clinical development.